Laser Surface Remelting of AISI 4140 Steel. Issue 1 (March 2020) - Zhao, Lirun; Hu, Zengrong; Wang, Xiaonan; Chen, Xiaming; Huan, Pengcheng; Zhang, Hai
Abstract: In order to improve the surface wear resistance and hardness, laser remelting was used to process AISI 4140 steel. The microstructure and the Vickers hardness of surface and cross-section of those samples were studied. The results shown the laser power was one of the most important facts, which affect the enhanced hardness and microstructure. After laser remelting, the the grain size of the sample surface was refined, and the hardness of the melted surface of AISI 4140 was improved. Compared to the base material it has about 313% incensement for samples processed with 130 W. It enhances the comprehensive mechanical properties dramatically.